Hydroxylation of ZnO/Cu(1 1 1) inverse catalysts under ambient water vapor and the water–gas shift reaction. (21st August 2019) - Orozco, Ivan; Huang, Erwei; Gutiérrez, Ramón A; Liu, Zongyuan; Zhang, Feng; Mahapatra, Mausumi; Kang, Jindong; Kersell, Heath; Nemsak, Slavomir; Ramírez, Pedro J; Senanayake, Sanjaya D; Liu, Ping; et al.
Abstract: The interaction of water vapor with ZnO/CuO x /Cu(1 1 1) surfaces was investigated using synchrotron-based ambient pressure x-ray photoelectron spectroscopy (AP-XPS) and density-functional theory (DFT) calculations. Cu(1 1 1) does not dissociate the water molecule. Cleavage of O–H bonds was seen with AP-XPS after depositing ZnO or preparing CuO x on the copper substrate. The results of DFT calculations show unique behavior for ZnO/CuO x /Cu(1 1 1), not seen on Cu(1 1 1), CuO x /Cu(1 1 1) or ZnO(0 0 0 ). The ZnO/CuO x /Cu(1 1 1) system binds water quite well and exhibits the lowest energy barrier for O–H bond cleavage. The presence of unsaturated Zn cations in the islands of ZnO led to high chemical reactivity. In order to remove the OH from ZnO/CuO x /Cu(1 1 1) and ZnO/Cu(1 1 1) surfaces, heating to elevated temperatures was necessary. At 500–600 K, a significant coverage of OH groups was still present on the surfaces and did react with CO during the water–gas shift (WGS) process. The final state of the sample depended strongly on the amount of ZnO present on the catalyst surface. For surfaces with a ZnO coverage below 0.3 ML, the adsorption of water did not change the integrity of the ZnO islands. On the other hand, for surfaces with a ZnO coverage above 0.3 ML, a ZnO → Zn x OH transformation was observed. This transformation led to a decrease in the WGS catalytic activity.